Impact of environmental regulation on government subsides of public-private partnership waste-to-energy incineration projects: evidence from 66 cities in China - Shen, Ye; Xu, Min; Cui, Caiyun; Xia, Bo; Skitmore, Martin; Moorhead, Matthew; Liu, Yong (Frontiers in Environmental Science, 2024)
Environmental regulation, as a vital component of public regulation in China, plays a crucial role in coordinating regional eco-efficiency, while the traditional hypothesis, Porter hypothesis, and uncertainty hypothesis offer three different perspectives for understanding the relationship between industry performance and environmental regulations. Based on the assumption of industry heterogeneity, 81 public-private partnership (PPP) waste-to-energy (WTE) incineration projects are analyzed using panel data from 66 cities within China during the period from 2013-2017 with the aims to reveal the underlying mechanism behind environmental regulation and the government subsides of public-private partnership waste-to-energy incineration projects by using multiple regression modeling. The results show that the impact of environmental regulation on government subsides of PPP WTE projects has demonstrated an "Inverted-U"-shaped relationship with an inflection point, of which an increase in environmental regulation is positively correlated with an increase in subsidies at first then a negative correlation developing later. The findings are significant in setting flexible environmental regulations according to the needs of regional economic and social development. In addition, they also supply a theoretical reference for promoting the WTE incineration industry's sustainable and healthy development.